Analisis prinsip kesantunan berbahasa Leech pada dialek Tanjungbalai dalam lingkungan keluarga melalui kajian pragmatik - Arera Vazira; Wan Nurul Atikah Nasution; Eva Mizkat; Rina Hayati Maulidiah (Jurnal Komunitas Bahasa, 2023)
This study aims to describe how the form of application and deviation of politeness principles in Leech language in a family environment of speakers in Tanjung Balai dialect. The method used in this research is descriptive qualitative. The data in this study are utterances spoken by fellow family member that show the forms of application and deviations of the principle of politeness in language. The results of this study indicate that the principle of language politeness is not always applied when communicating in everyday life by fellow family members. The politeness principle in question is the politeness principle developed by Leech, including: (1) field maxim, (2) generosity maxim, (3) appreciation maxim, (4) modesty maxim, (5) agreement maxim and (6) sympathy maxim. Thus utterances that deviate from Leech's politeness principle are more commonly found when communicating in the family environment, for in one family thats used as research, they pay little attention to the principles of politeness while talking between speakers and speech partners and the context/situation when communicating.Â